Availability of emergency contraception in large Brazilian municipalities: a guaranteed right? - Pinheiro, Ana Carolina Gomes; Alves, Bárbara Manuella Cardoso Sodré; Pedrosa, Claudia Mara; dos Reis, Tiago Marques; Bertoldi, Andréa Dâmaso; Zimmermann, Ivan Ricardo; Leite, Silvana Nair; Santana, Rafael Santos (Frontiers in Pharmacology, 2023)
Emergency Contraception (EC) is available in Brazil since 1996, when it was adopted as one if the family planning strategies and, in 1998, for use in services assisting victims of sexual violence. In the country, its use is regulated by guidelines. Its access through SUS (Unified Health System), however, does not seem to occur in a standardized manner. The aim of the study was to analyze the availability and barriers to accessing emergency contraception (levonorgestrel) in Brazilian municipalities with more than 500 thousand inhabitants. The survey was carried out by a form sent to the Municipal Health Departments (SMS) managers and a search on the list of standardized medicines by the hospitals in the same municipalities. The Basic Health Units were identified as the standard access places to EC. However, one of the obstacles mentioned is the need for a prescription for dispensing in almost 80% of the analyzed cities. Access in emergency situations at night and on weekends is also uncertain, since although 67% of the places stated that they dispense at the hospital level, the item was only standardized in 21% of the hospital lists. The difficult access this drug in the public system essentially tends to harm the poorest women, who are the ones who suffer most from the consequences of an unwanted pregnancy.